2016
DOI: 10.1016/j.healun.2016.01.906
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in 30 Lung Transplant Recipients

Abstract: had same diagnosis). At last child follow-up, age 9.6±6.8 yrs, the 20 children were reported otherwise healthy and developing well. Conclusion: Successful pregnancy is possible after lung transplantation, though caution is advised as these are extremely high-risk pregnancies with high incidences of prematurity, low birthweight infants, and maternal mortality. Close surveillance of these recipients is warranted due to the negative impact of rejection during pregnancy on graft and recipient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…This case series describes our single‐center experience with pregnancy after lung transplantation in Israel. Newborn outcomes in our cohort are significantly improved as compared to results reported in previously published case series 2–4,6 . Notably, we report the first series of two or more successful pregnancies in individual LTRs.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…This case series describes our single‐center experience with pregnancy after lung transplantation in Israel. Newborn outcomes in our cohort are significantly improved as compared to results reported in previously published case series 2–4,6 . Notably, we report the first series of two or more successful pregnancies in individual LTRs.…”
Section: Discussionsupporting
confidence: 52%
“…In terms of mortality, the same study reported a survival rate of 77% (23/30) with a maternal follow-up of 9.6 ± 6.8 years. 1,6 We observed two deaths in our cohort due to graft failure, translating into a survival rate of 75%, with one patient undergoing re-transplantation. These patients exceeded the median survival of 7.8 years following lung transplant, 12 before succumbing to graft failure at 8.5 and 14 years following the transplant, respectively.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations